Coordinated Restoration of Microgrids and Generation Units for Resilience Enhancement of Urban Power Grids - Xinrui Wang; Yuze Ji; Ruimin Tian; Helong Liu (Journal of Electrical and Computer Engineering)
During the urban power grid (UPG) restoration process after a major power outage, unit restoration may be delayed due to the shortage of black-start resources. With the development of microgrids (MGs), various restoration resources are integrated into MGs. Taking full advantage of the restoration value of MGs and coordinating the restoration process of units and MGs can accelerate the restoration speed of UPG. This paper proposes a novel coordinated restoration method for MGs and UPG. Firstly, a distributed coordination scheme for unit restoration in UPG and service restoration in MGs is proposed. Then, taking into account of the restoration and operation constraints of power grid, the unit restoration model of UPG and MG service restoration model are constructed, respectively. Considering the independent management and information privacy of the UPG and MGs, a distributed optimization algorithm is adopted to solve the models. The effectiveness and superiority of the proposed method are verified using a coupling system.